2013
DOI: 10.1159/000355758
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS-7 Expression Increases in the Early Stage of Angiotensin II-Induced Renal Injury in Elderly Mice

Abstract: Background/Aims: We investigated the recently described family of proteinases, a disintegrin and metalloproteinase with thrombospondin motifs (ADAMTs), and matrix metalloproteinases (MMPs) as inflammatory mediators in inflammatory kidney damage by studying ADAMTS-1, -4, and -7 and MMP-9 expression in elderly mouse kidneys after angiotensin II (Ang II) administration. Methods: Ang II (2.5 µg/kg/min) or norepinephrine (8.3 µg/kg/min) was subcutaneously infused in old mice. Renal injury was assessed by hematoxyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Indeed, ADAMTS-7 has been shown to promote vascular remodeling via thrombospondin-1 [23]. ADAMTS-7 levels were correlated with inflammatory markers such as TNF-α and NF-κB in different inflammatory conditions and diseases [24][25][26], as well as in organ injury such as angiotensin-II renal injury [27]. Interestingly, recent findings suggested that activation of M1 but not M2 macrophages plays an important role in cardiac remodeling after myocardial infarction in rats [28].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, ADAMTS-7 has been shown to promote vascular remodeling via thrombospondin-1 [23]. ADAMTS-7 levels were correlated with inflammatory markers such as TNF-α and NF-κB in different inflammatory conditions and diseases [24][25][26], as well as in organ injury such as angiotensin-II renal injury [27]. Interestingly, recent findings suggested that activation of M1 but not M2 macrophages plays an important role in cardiac remodeling after myocardial infarction in rats [28].…”
Section: Discussionmentioning
confidence: 99%
“…For example, THP-1 monocytes show increased ADAMTS-7 expression after stimulation with interferon-γ or TNF-α 11 and cartilage explants increase ADAMTS-7 expression after TNF-α or interleukin-1β stimulation 26 . Furthermore, angiotensin II-treatment of mice associated with inflammatory kidney damage induces renal ADAMTS-7 expression 27 and ADAMTS-7 is elevated in collagen-induced arthritic mice 6 . It is also possible that some of the CD68 stained cells in the analyzed carotid plaques in our study are in fact SMC-derived cells displaying macrophage markers.…”
Section: Discussionmentioning
confidence: 99%
“…Although ADAMTS‐7 related to kidney damage and atherosclerosis, it is suggested that ADAMTS‐1 and ‐14 are associated with fibrosis . Also, it is claimed renal ADAMTS‐7 expression was induced by Ang II in elderly mice and suggested the overexpression of ADAMTS‐7 might contribute to early inflammatory kidney damage associated with aging . In the study of murine remnant kidney model, Yang et al observed a significant increase in the average gene expression of ADAMTS‐1 and several profibrotic genes including MMP‐2, MMP‐9, TIMP‐1 and fibroblast specific protein‐1.…”
Section: Discussionmentioning
confidence: 99%